Maternal outcomes in placenta accreta spectrum (PAS) at tertiary care hospital - Yasmin, Maryam; Un-Nisa, Fakhar-; Pervez, Maria; Jalal, Robina; Khokhar, Naeem Akhtar; Begum, Amna (Journal of Neonatal Surgery, 2025)
Background: A severe obstetric disease that has been receiving more attention recently because of its increasing prevalence is placenta accreta spectrum disorder (PAS). It has a major effect on the health of the mother and the newborn. Objective: The aim of this study was to determine the maternal outcomes in placenta accreta spectrum. Materials and method: The present cross- sectional study was conducted at the gynecology department Lady Reading hospital Peshawar form November 2024 to April 2025 after taking approval from the research committee of the hospital. The sample size was determined through WHO calculator and was 41. For sample collection non probability method was used. Pregnant women of different age groups diagnosed with PAS were included in this study. Before data collection in elective cases and following surgery in emergency patients, consent was obtained. The research assessed maternal outcomes. The placenta remained intact since it was impossible to remove owing to the considerable involvement of the bladder. A proforma that had been previously created was used to record the maternal and fetal outcomes. The variables were shown as means, standard deviation, frequency, and percentages. To determine the relationship between different parameters and maternal outcome, the chi square test was used. A 0.05 p-value was considered significant. Results: A total of 41 pregnant women with placenta accreta were included out of which 14(34.1%) cases had cesarean section and 27(65.8%) had emergency delivery. The majority of participants 34(82.9%) of the overall study population were 21-30 years followed by age group 30 or above 4 (9.7%) and age group 20 years 3 (7.3%) respectively. 14 (34.1%) of the patients received multidisciplinary care from cardiovascular surgeons and urologists. 3 (7.3%) had ureter and bowel injury, while 6 cases (14.6%) involved bladder damage. 26 patients (63.6%) experience blood loss and needed blood transfusions . 13 (31.7%) individuals had a wound infection, and 11 (25.7%) underwent reopening laparotomy. Following surgery, 53.6% needed to remain in the hospital for more than seven days. 5 (12.1%) of the newborns began their lives in the neonatal intensive care unit, while 19 (46.3%) mothers were sent to the critical care unit. Two (4.8%) moms lost their lives during the delivery process. There was no discernible correlation between maternal outcome and factors such as organ damage, reopening laparotomy, MDT presence, or kind of caesarean section. Conclusion Our study concluded that placenta accreta spectrum is associated with significant maternal morbidity and mortality and its most prevalent maternal complication is hemorrhage.